Skin substitutes: from conventional to 3D bioprinting - Deepa, C.; Bhatt, Anugya (Journal of artificial organs, 2025)
Three-dimensional bioprinting is getting enormous attention among the scientific community for its application in complex regenerative tissue engineering applications. One of the focus areas of 3-D bioprinting is Skin tissue engineering. Skin is the largest external organ and also the outer protective layer is prone to injuries due to accidents, burns, pathologic diseases like diabetes, and immobilization of patients due to other health conditions, etc. The demand for skin tissue and the need for an off-the-shelf skin construct to treat patients is increasing on an alarming basis. Conventional approaches like skin grafting increase morbidity. Other approaches include acellular grafts, where integration with the host tissue is a major concern. The emerging technology of the future is 3D bioprinting, where different biopolymers or hybrid polymers together provide the properties of extracellular matrix (ECM) and tissue microenvironment needed for cellular growth and proliferation. This raises the hope for the possibility of a shelf skin construct, which can be used on demand or even skin can be printed directly on the wound site (in-situ printing) based on the depth and complex structure of the wound site. In the present review article, we have tried to provide an overview of Skin tissue engineering, Conventional advancement in technology, 3D bioprinting and bioprinters for skin 3D printing, different biomaterials for skin 3D bioprinting applications, desirable properties of biomaterials and future challenges.